2 | ÷ | 3 | × | x | + | 2 | = | 3 | ÷ | 4 | × | ( | x | − | 3 | ) |
Left side of the equation = | 2 3 | x | + | 2 |
2 3 | x | + | 2 | = | 3 | ÷ | 4 | × | ( | x | − | 3 | ) |
Right side of the equation = | 3 4 | ( | x | − | 3 | ) |
2 3 | x | + | 2 | = | 3 4 | ( | x | − | 3 | ) |
Right side of the equation = | 3 4 | x | − | 3 4 | × | 3 |
= | 3 4 | x | − | 9 4 |
2 3 | x | + | 2 | = | 3 4 | x | − | 9 4 |
2 3 | x | − | 3 4 | x | = | - | 9 4 | − | 2 |
- | 1 12 | x | = | - | 9 4 | − | 2 |
- | 1 12 | x | = | - | 17 4 |
17 4 | = | 1 12 | x |
1 12 | x | = | 17 4 |
x | = | 17 4 | ÷ | 1 12 |
= | 17 4 | × | 12 |
= | 17 | × | 3 |
x | = | 51 |